A Study on the Influence of Mining Depth on the Stress Distribution Characteristics of Stope Surrounding Rock. (23rd September 2022) - Li, Shaobo; Wang, Lei; Ren, Qihan; Zhu, Chuanqi; Liu, Huaqiang; Liu, Huaiqian; Chen, Lipeng
Abstract : The occurrence of severe mine pressure in stope is of high risk, and the mining depth is the main control factor which affecting the occurrence of mine pressure in stope. In order to study the influence law of mining depth on stope strata behavior, taking 11318E fully mechanized working face in Xieqiao Coal Mine of Huainan Mining Group as the engineering background, the stress distribution and evolution characteristics of stope surrounding rock under mining depth were studied by similar material simulation. And the evolution laws of mechanical characteristics of stope surrounding rock under different mining depths of 600 m and 1200 m were simulated. It is concluded that with the increase of mining depth, the damage range of surrounding rock on the mining field increases significantly. The initial collapse of the immediate roof above the working face is not affected by the mining depth. The periodic weighting caving step decreases with the increase of mining depth, and the height of two zones above the working face increases with the increase of mining depth. The stress transfer and evolution characteristics of the strata above the stope were revealed. The increase of front caving angle indicates that the pressure on the support of the working face is greater, indicating that the support of the working face should be strengthened with the increase of mining depth. The research results have a guiding role in the control of surrounding rock and disaster prevention of deep mine stope.